Manajemen Pembelajaran Bahasa Arab Di LPQ Tahfidzul Qur’an Ar-Rahman - Azmi, Khairul (STAINI Press, 2022)
The world of education continues to grow with the challenges of today's times. He taught Arabic only in formal educational institutions, but now he has started studying in informal institutions, as in lpq Tahfidzul Qur'an Rahman. Learning management is essential to achieving the goals of educational institutions, not least the management of learning in Arabic. The research aims to illustrate the implementation of the Arabic Language Learning Department in informal institutions. The search method is a qualitative method. Data collection techniques use surveillance, interviews and documents, while data validation testing techniques use triangulation. The results showed that the Arabic language learning department at Tahfidzul Qur'an Rahman, which includes planning, organization, implementation, control and evaluation, went very well. This conclusion is based on working meetings that plan annual and classroom programs, organize Arabic language learning programs as planned, good, effective and effective in the implementation of learning contracts, supervision/ supervision at all times, and intensive evaluation